2020
DOI: 10.3390/ijerph17155505
|View full text |Cite
|
Sign up to set email alerts
|

Case Ascertainment on Australian Registers for Acute Rheumatic Fever and Rheumatic Heart Disease

Abstract: In Australia, disease registers for acute rheumatic fever (ARF) and rheumatic heart disease (RHD) were previously established to facilitate disease surveillance and control, yet little is known about the extent of case-ascertainment. We compared ARF/RHD case ascertainment based on Australian ARF/RHD register records with administrative hospital data from the Northern Territory (NT), South Australia (SA), Queensland (QLD) and Western Australia (WA) for cases 3–59 years of age. Agreement across data sources was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In addition to wider and more representative coverage of population groups across Australia, a major strength of this study is the augmentation of clinically confirmed register-derived RHD cases with hospitalization records, reducing biases resulting from studying register data alone. 20 This bias is best illustrated by noting that our sensitivity analyses of register-derived individuals consistently estimated lower absolute progression probabilities to the study cohort.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In addition to wider and more representative coverage of population groups across Australia, a major strength of this study is the augmentation of clinically confirmed register-derived RHD cases with hospitalization records, reducing biases resulting from studying register data alone. 20 This bias is best illustrated by noting that our sensitivity analyses of register-derived individuals consistently estimated lower absolute progression probabilities to the study cohort.…”
Section: Discussionmentioning
confidence: 95%
“…Australian RHD control efforts (including registers) have been mostly directed at Indigenous populations, capturing a higher proportion of Indigenous RHD cases. 8 , 20 While the Indigenous burden is high in absolute terms, the average severity of cases may be lower when compared to other groups. This is supported by progression estimates in the register-derived (mostly Indigenous) cohort which had generally lower progression probabilities than the multi-jurisdictional study cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age was included in our model as a demographic parameter. Agenson et al ( 40 ) indicated that advanced age had an adverse effect on mortality. In sub-Saharan Africa, RHD is thought to be responsible for up to 32% of heart failure cases ( 41 ).…”
Section: Discussionmentioning
confidence: 99%